ISOPROTERENOL SEBAGAI MODEL INFARK MIOKARDIAL AKUT PADA TIKUS WISTAR - Wahyu Widiyaningsih; Sugiyanto Sugiyanto; Sitarina Widyarini; Suwidjiyo Pramono (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Decreased oxygen supply and necrosis in the heart muscle cells can lead to acute myocardial infarction. Free radical compounds can lead to oxidative stress in the heart muscle and lead to myocardial infarction. Isoproterenol is a non-selective β-adrenergic agonist can lead to acute myocardial infarction in large doses. The purpose of this study was to validate the model of acute myocardial infarction. This study using male Wistar rats aged two months as the test animal. Male Wistar rats divided into two groups: control group and treatment group. The control group treated with physiological saline and the treatment group treated with isoproterenol 85 mg/kg BW. Isoproterenol administered subcutaneously for two doses with an interval of 24 hours. After 48 hours of the isoproterenol first administration, rat heart rhythm's records with an electrocardiogram (ECG). Furthermore, the rats sacrificed and performed a necropsy. The left ventricle part in the cross section for the macroscopic observation (extensive infarction) with triphenyl tetrazolium chloride (TTC) staining, microscopic observation of infarction with hematoxylin-eosin staining (HE) and immunohistochemical (IHC) to observe the expression of caspase-3. The ECG of isoproterenol group showed elevation in the ST segment. TTC staining shows the expansion of the infarct area. The HE staining showed the typical image of myocardial infarction and the IHC staining results showed an increase in the expression of caspase-3. The results showed that isoproterenol can be use as a model myocardial infarction with parameters of infarction are ECG changes, TTC staining of infarct broad macroscopic image, a histopathological image of heart and apoptosis with the expression of caspase-3. Key words: Isoproterenol, acute myocardial infarction, cardiac histopathology